Aplikasi Radien untuk Pengolahan Data Rekam Medis dengan Microsoft Visual Studio 2010 - Shavira Handayani Putri; Yuda Syahidin; Meira Hidayati (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2021)
This study aims to design an integrated patient development record complete information system at Bina Sehat General Hospital in Bandung. The research method that the author used in this research is a use qualitative research method with a descriptive approach. And for the software method used by the author in this study, the Waterfall development method is used. From the results of the research that has been done by the author, it was found, including the processing of the integrated patient development record completeness system that was running less effectively, there was still incomplete integrated patients’ development record. Therefore, the authors designed an information system the completeness of patient progress record integrated with the programing language used was Microsoft Visual Studio 2010, and the database used was Microsoft Access 2016. The suggestion that the author gave was the need to develop an integrated patient development record complete information system to facilitate processing the required information, the need for socialization about filling out patient progress record integrated to all officers.